The Polish physiotherapists' state of knowledge about the act on the profession of physiotherapist - Małgorzata Kulesa-Mrowiecka; Joanna Piech; Maciej J. Dańko; Mateusz Stec; Dominika Bryłowska; Iwona Kowalska-Bobko (Nofer Institute of Occupational Medicine, 2021)
Background Work on the Act on the Profession of Physiotherapist had been conducted since the 1990s. However, it was not until October 2015 that the legal regulations were eventually introduced, following which physiotherapists gained professional independence and became a profession of public trust. The aim of the study was to assess the factors influencing the knowledge of these legal regulations among physiotherapists. Material and Methods The study involved 399 physiotherapists and physiotherapy students (28.8±5.9 years old) who completed an anonymous questionnaire, in the form of a knowledge test, consisting of 24 questions on the general aspects of the reference Act. Results Overall, 30.3% of the respondents proved to have a significant knowledge about the rights and obligations resulting from the Act. The physiotherapists who were entered into the National Register of Physiotherapists (2.6 times) and residents of large cities (1.8 times) had a greater knowledge of the Act. There was a correlation between seniority and gender, and the knowledge of legal regulations. Conclusions The main factors influencing the state of knowledge about the Act are the entry to the National Register of Physiotherapists, the place of residence and seniority. This proves better access to up-to-date information in cities and a greater interest in the Act among those people who have obtained the right to practice their profession. Med Pr. 2021;72(4):407-14